The need of creating a new nominal creepage distance in accordance with heaviest pollution 500 kV overhead line insulators. (April 2018) - Arias Velásquez, Ricardo Manuel; Mejia Lara, Jennifer Vanessa
Abstract: The flashovers on insulators, caused by severe pollution, has posed the biggest threat on the safe operation of power systems the insulators contamination, and it is an important problem, special in polluted. The aperiodic occurrence of widespread contamination related outages cause serious damages to the transmission lines, the worst behavior is up to 500 kV overhead lines. The exceptional level of pollution measured on those insulators, especially for the bottom surface for the non-soluble salt deposit density (NSDD) component, where the values are outside of the standard limit given in the currently IEC standard. The results provide important reference for the insulators design, maintenance of operational transmission line insulators and flashover warnings. It should be highlighted that results fall out of the limit of the IEC standard and that in order to plot those values in the graph the limits for the highest NSDD values have been increased from 4 to 20 g/cm 2 . This clearly shows the unusually high values of the NSDD components measured on those insulators. The case study has been realized on 837, 000 insulators for 9000 towers in 500 kV powers lines. This clearly shows the unusual characteristics of the coast and desert environment of the 500 kV overhead lines, and the needs of update in the IEC standards has been researched. Highlights: The flashovers on insulators, caused by severe pollution, has posed the biggest threat on the safe operation. Unusual contamination characteristics of the coast and desert environment of the overhead line. Needs of creation of a new minimum nominal creepage distance.